Effect of Acute Physical Exercise on Executive Functions and Emotional Recognition: Analysis of Moderate to High Intensity in Young Adults - Aguirre-Loaiza, Haney; Arenas, Jaime; Arias, Ianelleen; Franco-Jímenez, Alejandra; Barbosa-Granados, Sergio; Ramos-Bermúdez, Santiago; Ayala-Zuluaga, Federico; Núñez, César; García-Mas, Alexandre (Frontiers in Psychology, 2019)
Physical exercise (PE) is associated with cognitive changes and brain function. However, it is required to clarify the effect of PE in different intensities, population groups conditions and the EF duration over different cognitive domains. Besides, no studies are known to have evaluated the contextual emotional recognition. Therefore, we studied the effect of acute PE of moderate intensities up to higher ones to the executive functions and the contextual emotional recognition. The participants were evaluated and classified in two experiments according to the IPAQ short form self-report and control measures. In both experiments, the groups were randomized, controlled, and exposed to one session of indoor cycling through intervals of high measure intensity (75-85% HRmax). Experiment 1comprised young adults who were physically active (PA) and healthy, apparently (n= 54, Mage= 20.7, SD= 2.5). Experiment 2 involved young adults who were physically inactive (IP) and healthy, apparently (n= 36, Mage= 21.6, SD=1.8).The duration was the only factor that varied: 45 min for PA and 30 min for PI. The executive functions were evaluated by the Stroop, TMT A/B and verbal fluency, and the emotional recognition through a task that includes body and facial emotions in context, simultaneously. The analysis of factorial mixed ANOVA showed effects on the right choices of the indoor cycling groups in the PA, and the time response in PI. Also, other effects were observed in the controlled groups. TMT-A/B measures showed changes in the pretest-posttest measures for both experiments. Verbal fluency performance favored the control group in both experiments. Meanwhile, the emotional recognition showed an effect of the PE in error-reduction and enhanced the scores in the right choices of body emotions. These results suggest that the EF with intensities favored cognitive processes such as inhibitory control and emotional recognition in context. We took into account the importance of high-complexity tasks design that avoid a ceiling effect. This study is the first on reporting a positive effect of PE over the emotional contextual recognition. Important clinical and educational implications are presented implications which highlight the modulatory role of EF with moderate to high intensities.